Cutaneous Polyarteritis Nodosa Presenting with Digital Gangrene - Kumar, K Jagadish; Ramaswamy, Subramanian; Saldana, Karen (Journal of Nepal Paediatric Society, 2016)
Cutaneous polyarteritis nodosa is a vasculitis with characteristic manifestations like tender subcutaneous nodules, livedo reticularis, cutaneous ulcers and necrosis. Diagnosis requires histopathologic evidence of necrotizing inflammation of the medium and small arteries. We report a six year old girl with cutaneous PAN with gangenous changes of the fingertips which responded to methylprednisolone. J Nepal Paediatr Soc 2016;36(1):82-84.